TOP-GATE TRANSISTOR ARRAY SUBSTRATE - CHENG Huang-Chung; HUANG Yu-Chih; YANG Po-Yu; CHIANG Shin-Chuan; LI Huai-An (My University, 2013)
A top-gate transistor array substrate includes a transparent substrate with a plane, an ion release layer, a pixel array, and a first insulating layer. The ion release layer is disposed on the transparent substrate and completely covers the plane. The pixel array is disposed on the ion release layer and includes a plurality of transistors and a plurality of pixel electrodes. Each of the transistors includes a source, a drain, a gate and a MOS (metal oxide semiconductor) layer. The drain, the source and the MOS layer are disposed on the ion release layer. The pixel electrodes are electrically connected to the drains respectively. The gate is disposed above the MOS layer. The first insulating layer is disposed between the MOS layers and the gates. The MOS layer contacts the ion release layer. The ion release layer can release a plurality of ions into the MOS layers.